Phytic acid content and in-vitro digestibility of several cereal and legume types treated with different processes - Ertop, Muge Hendek; Bektaş, Müberra (National University of Food Technologies, 2021)
Introduction. The present study aims to determine the relationship between phytic acid (PA) content/digestibility rate of the grains, which are widely consumed in daily diet, and the methods often used in preparing food for consumption. Materials and methods. In this study, the dephytinization effect of soaking (for 12 h), boiling (at 100 degrees C for 1 h), autoclaving (at 121 degrees C for 15 min), fermentation (at 25-27 degrees C), and germination processes on several grains were studied. PA contents, Mineral Digestibility (MD, %), and Protein Digestibility (PD, %) were determined, and their effects comparatively evaluated before and after processes. Results and discussion. There were decreases in PA contents in legumes and cereals for all the methods applied. Fermentation (<800 mg/100 g) of the flour and germination for the other samples (<700 mg/100 g) were found to yield more effective results to PA degradation. Between 20-70% reduction by fermentation and 50-80% reduction by germination of PA contents in the samples were found. Moreover, MD level in cereals, which was especially low before germination, increased up to 2 times after the germination. PD, %, was found to increase with the effect of the processes, except for boiling and soaking. Especially germination process was more effective in tems of PD. Increasing rate of PD for ten bean samples was up to 200%. Wheras the PA contents in the cereal flour samples after their spontaneous fermentation were decreased, their digestibility values were increased statistically (p<0.05). Conclusions. All processes applied such as soaking, fermentation, or heat treatments, which are widely used to preparation of the grains, provide an advantage in dephytinization at different rate. Combined use of techniques such as soaking, and boiling which are used in the preparation of various cereal and legume products for consumption, is also be effective in terms of nutritional quality and their combinations were proposed.

WOS:000751894100005
Keywords: Phytic Acid; Bioavailability; Digestibility; Cereal; Legume; 2. Zero hunger